2015
DOI: 10.1111/aos.12757
|View full text |Cite
|
Sign up to set email alerts
|

Detection of retinal changes in idiopathic Parkinson's disease using high‐resolution optical coherence tomography and heidelberg retina tomography

Abstract: ABSTRACT.Purpose: The study was performed to analyse the retina of patients with Parkinson's disease (PD) for morphological changes compared to healthy controls (HC) using spectral-domain optical coherence tomography (SD-OCT) and confocal scanning laser ophthalmoscopy. Methods: We enrolled 108 patients with idiopathic PD and 165 HC. All study participants underwent an ophthalmological examination to exclude ophthalmological disorder potentially interfering with the retinal analyses. Peripapillary retinal nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 33 publications
0
32
0
3
Order By: Relevance
“…Despite that early evidence on retinal thinning in iPD, several subsequent studies have provided conflicting results. Whereas some authors have reported that iPD patients have a significant and marked thinning of the macula and its inner retinal layers, others have evidenced outer retinal layer thinning, or even thickening, and some have failed to find any differences . The variability in scanning protocols, acquisition parameters and built‐in segmentation algorithms across different OCT systems is a well‐established limitation for comparing the results of different studies and could account for the discrepancies found in the literature regarding retinal alterations in iPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that early evidence on retinal thinning in iPD, several subsequent studies have provided conflicting results. Whereas some authors have reported that iPD patients have a significant and marked thinning of the macula and its inner retinal layers, others have evidenced outer retinal layer thinning, or even thickening, and some have failed to find any differences . The variability in scanning protocols, acquisition parameters and built‐in segmentation algorithms across different OCT systems is a well‐established limitation for comparing the results of different studies and could account for the discrepancies found in the literature regarding retinal alterations in iPD.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some authors have reported that iPD patients have a significant and marked thinning of the macula 10,12-14 and its inner retinal layers, 8,9,11,[21][22][23][24][25][26] others have evidenced outer retinal layer thinning, 27 or even thickening, 11,24 and some have failed to find any differences. [28][29][30][31][32][33][34] The variability in scanning protocols, acquisition parameters and built-in segmentation algorithms across different OCT systems is a well-established limitation for comparing the results of different studies 35 and could account for the discrepancies found in the literature regarding retinal alterations in iPD. Specifically, the differences in acquisition speed and axial resolution between time-domain and spectral-domain OCTs might explain why studies using older time-domain OCT devices (eg, Stratus) only detected significant differences between iPD patients and controls when absolute differences in thickness were greater than 10 μm, 20,36 whereas studies using spectraldomain OCTs have yielded significant results with differences from 2 to 7 μm in thickness regardless of the area analyzed, 7,9,12,24,25,27,34,[37][38][39][40] which is consistent with the magnitude of inner retinal thinning observed in our E46K-SNCA cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, changes in retinal morphology have been investigated using time or spectral domain (SD) OCT, which has shown thinning of the RNFL 6, 7 either peripapillary 8 , in different retinal areas 9 or in the fovea 1013 and also thinning of the macula 7, 14 whereas others found no differences of the RNFL 13, 15 . Furthermore, alterations in the retinal vascular architecture of PD patients have recently been detected 16 .…”
Section: Introductionmentioning
confidence: 99%
“…After 2 years, RPE hypopigmentation prevalence was similar to baseline, 28.9%. We are not aware of previous clinical reports of RPE hypopigmentation in idiopathic PD, although PD perturbations of other retinal structures are documented (e.g., macular and retinal nerve fiber layer thinning [19] and inverse correlation of central minimum thickness with Hoehn–Yahr stage [20]). Retinal thickness distinguishes advanced PD patients from healthy persons [21].…”
Section: Discussionmentioning
confidence: 99%